Strategi Kepala Madrasah dalam Meningkatkan Prestasi Siswa di Madrasah Ibtidaiyah Unggulan Sabilillah Lamongan - Widianto, Suheri; Al-Kadhafi, Muhammad Jamaluddin (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their own potential, personality, intelligence, noble character, and the skills needed by themselves, society, nation and state. Indonesian National Education based on Pancasila aims to develop the potential of students to become human beings who believe in and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible country.The success of a nation can be seen from the extent to which its people take education. The higher the education pursued by the community, the more advanced the nation will be. Quality education is the key to building competent human beings and producing graduates as expected. In realizing quality education, it is necessary to implement programs that focus on improving the quality and activities of education in schools.Quality Education is not only seen from the quality of its graduates, but includes the efforts made by the School to meet educational needs in accordance with applicable quality standards. In realizing quality education, a leader who has a strong mentality is needed, is able to overcome various problems and obstacles, and has the courage to make educational innovations.In school management, the school principal, according to his function, can understand the needs of the school he leads so that teacher competence is not only the competence he had before, but can increase and develop in a better direction so that teacher professionalism will be realized. And also the Principal as a leader or a good leader must be able to strive to increase student achievement.The increase in achievements that have been achieved as evidenced by the many achievements in the Sabilillah Lamongan Superior Madrasah Ibtidaiyah School, Sabilillah Lamongan Superior Madrasah Ibtidaiyah (MIUS) which stands under the auspices of the Sabilillah Lamongan Foundation. Accredited